Flight attraction of Spodoptera littoralis (Lepidoptera, Noctuidae) to cotton headspace and synthetic volatile blends - Borrero-Echeverry, Felipe; Becher, Paul G.; Birgersson, Göran; Bengtsson, Marie; Witzgall, Peter; Saveer, Ahmed M. (Frontiers in Ecology and Evolution, 2015)
The insect olfactory system discriminates odor signals of different biological relevance, which drive innate behavior. Identification of stimuli that trigger upwind flight attraction towards host plants is a current challenge, and is essential in developing new, sustainable plant protection methods, and for furthering our understanding of plant-insect interactions. Using behavioral, analytical and electrophysiological studies, we here show that both females and males of the Egyptian cotton leafworm, Spodoptera littoralis (Lepidoptera, Noctuidae), use blends of volatile compounds to locate their host plant, cotton, Gossypium hirsutum (Malvales, Malvaceae). Female S. littoralis were engaged in upwind orientation flight in a wind tunnel when headspace collected from cotton plants was delivered through a piezoelectric sprayer. Although males took off towards cotton headspace significantly fewer males than females flew upwind towards the sprayed headspace. Subsequent assays with antennally active synthetic compounds revealed that a blend of nonanal, (Z)-3 hexenyl acetate, (E)-β-ocimene, and (R)-(+)-limonene was as attractive as cotton headspace to females and more attractive to males. DMNT and (R)-(-)-linalool, both known plant defense compounds may have reduced the flight attraction of both females and males; more moths were attracted to blends without these two compounds. Our findings provide a platform for further investigations on host plant signals mediating innate behavior, and for the development of novel insect plant protection strategies against S. littoralis.